STABILISASI SISTEM NONLINIER DENGAN PENGENDALI SWATALA - Nur Alif Mardiyah (Jurnal Gamma, 2006)
This research studied the design of a adaptive control for nonlinier systemthat is reactor process which has multiple steady states, two stable steady states and one unstable steady state. The study is based on a simulation of adaptif pole placement control system using MATLAB ver 5.3. The pole placement adaptive controller can only control the reactor process at range of 330.90K up to 3500K in the range of 3900K up to 404.90K.